Immune-iron homeostasis deciphers resistance divergence to Riemerella anatipestifer in ducks - Zou, Mengyun; Xiong, Xiaolan; Zhang, Weihong; Wei, Yue; Tang, Weiguo; Wei, Qipeng; Huang, Cong; Kang, Zhaofeng; Xie, Jinfang; Huang, Jiangnan (Frontiers in Microbiology, 2025)
Riemerella anatipestifer (RA) causes substantial economic losses in global waterfowl production. This study compared immune responses and iron metabolism of ducks against RA infection between commercial White Kaiya ducks (WK) and native Ji’an Red-feathered ducks (JR), and between resistant (R) and susceptible (S) individuals within each breed. Results revealed JR ducks exhibited lower morbidity (85.63% vs. 100%) and mortality (68.75% vs. 88.76%) than WK ducks under identical infection conditions. Susceptible individuals in both breeds showed severe weight loss, splenomegaly, and multiorgan histopathological damage. Conversely, phenotype-specific resilience differed by breed: R-JR ducks maintained stable body weight, normal spleen indices, and minimal lesions versus weight loss, splenomegaly, and pathological persistence in R-WK ducks. Furthermore, S-JR ducks exhibited elevated tumor necrosis factor-α (TNF-α) with down-regulated IgA, interferon-γ (IFN-γ), interleukin-22 (IL-22), IL-4, and IL-10 whereas R-JR ducks maintained stable IgA/Th1/Th2 cytokines with elevated IL-17A. In contrast, S-WK ducks exhibited elevated IgM/IgG/TNF-α with static IgA levels, and decreased IL-17A, while R-WK ducks showed lower IgM with stable IgG/Th1/Th2/Th17 level S relative to S-WK ducks. Furthermore, pathological iron accumulation occurred in all infected WK ducks but not resistant JR ducks. Collectively, these breed-specific differentials highlight JR ducks’ coordinated immune-iron homeostasis versus WK ducks’ cytokine and iron dysregulation, providing insights for disease-resistant breeding strategies.